Kajian Pengaruh Kebisingan, Temperatur, Dan Pencahayaan Terhadap Performansi Kerja Operator Produksi Dengan Pendekatan Desain Eksperimen (Studi Kasus PT. Reksa Prima Daya) - Lobes Herdiman; Bambang Suhardi; Ade Herman Setiawan (Performa: Media Ilmiah Teknik Industri, 2007)
Physical working environment is assumed as an ideal environment as a worker conducts the activity effectively and efficiently with good quality productivity assessment. Noise, temperature, and lighting factors of the working environment represent a consequence of the working pressure and working performance degradation. The result of the calculation of physically work environment of product division PT.Reksa Prima Daya, the average of noise level is 85 dB, temperature 32 0C, and lighting 150 lux. The highest points of noise level is 85 dB for eight working hours each day, the lowest turning points of temperature is 18 0C in a room and the highest is 30 0C, and the minimum level of lighting for machine and arrangement is 300 lux. The control and the management of noise, temperature, and lighting factors required to advance the operator working performance The aim of this research is to determine the noise level (60dB, 75dB, 85dB), temperature level (24ºC, 27ºC, 32ºC), and lighting level (150lux, 200lux, 300lux) of production division PT. Prima Reksa Daya sustaining the operator working performance and analyzing the selected level of it. This research applies the method of factorial experiment design to determine the significant influential factors of work performance and to determine the optimal level of the supporting factors of work performance. This research is conducted in climate laboratory of the Faculty of Engineering, Sebelas Maret University. The result of this research indicating that noise, temperature and lighting factors provide significant impact in supporting the operator working performance and the optimal condition are on the level 60dB of noise (level 1), 24ºC of temperature (level 1), and 300lux of lighting (level 3) for the duration of work performance 66.72 seconds. The optimal condition can improve the work performance 17.8 seconds (15%) for the actual condition of the company by 84.4 seconds to compile a working table.